Elephant with fun finger puppet (Cottage Farm, England Igloo Books Ltd, 2019)
Join Elephant as he plays and laughs with his jungle friends, this finger puppet book is wonderfully fun and interactive for babies
English Stories
2 23
Keywords: English Stories